Niveles de sustitución de forraje hidropónico de maíz (Zea Mays) en el alimento concentrado y su influencia en el rendimiento productivo de aves criollas mejoradas en etapa de engorde en Zúngarococha 2024 - Tananta Chashnamote, Paolo Cesar (2025)
The present research evaluated the impact of the substitution of hydroponic corn forage (Zea mays) in concentrated feed on the productive performance of improved native birds during the fattening stage in Zúngarococha, 2024. This research seeks to provide sustainable nutritional alternatives to optimize poultry production performance in the region. The main objective was to determine how different levels of inclusion of hydroponic maize forage (0%, 5%, 10%, 15% and 20%) affect key variables such as final weight, weight gain, feed intake, feed conversion and efficiency. Food. To do this, a completely randomized experimental design was used with five treatments and twenty replications, covering a total of 100 improved landracebirds. The data obtained were analyzed using ANOVA and the Tukey Test to identify significant differences between treatments. The results indicated that the treatment with 5% inclusion of hydroponic forage (T1) was the most efficient, achieving higher values of final weight (2783.15 gr), weight gain and feed efficiency, while levels above 10% negatively impacted these variables. No cases of mortality were recorded in any of the treatments. It is concluded that the moderate inclusion of hydroponic forage in the diet of improved landraces represents a viable alternative to improve productive performance without compromising the health of the birds. It is recommended to limit inclusion to a maximum of 10% and consider supplementation of FVH with other nutritional inputs. These strategies could be implemented in local poultry systems to promote more efficient and sustainable production.